Analysis of the Recruitment of Members of the Indonesian National Police (Case Study of the West Java Regional Mobile Brigade) - Cecep Suarha (Journal of Applied Management and Business Administration, 2023)
This study aims to determine, describe and analyze the Recruitment of Members of the Indonesian National Police in Brimob related to the recruitment process, the source of recruitment, the factors that must be considered in the selection, the problems found in the selection and the role of recruitment and selection. The research method used in this study is a descriptive research method with a qualitative approach. The data collection techniques used in this study were interviews, observation and documents. Based on the results of research and discussion, it was concluded that the Recruitment Analysis of the Members of the Indonesian National Police (Case Study of the West Java Regional Mobile Brigade) in the Recruitment Process Brimob members from AKPOL, BINTARA, and TAMTAMA, still have not carried out the selection of members of the National Police especially in Brimob successively or every year there is no Brimob quota opening so there is a shortage of Polri personnel in Brimob, there are still participants who did not prepare themselves for selection, especially in health from starting to check eyes, teeth, tonsils, varicoceles and varicose veins, there are still participants who after graduating from selection and continued with police education but in the education process must be excluded due to mental factors, stress , and other health, there are still members who after graduating from general education, were then transferred to Brimob quite a bit on the grounds that Brimob was always assigned out of Java and demanded daily for training.